PENGARUH PERUBAHAN RETURN ON ASSETS, PERUBAHAN PERATING PROFIT MARGIN, DAN UKURAN PERUSAHAAN TERHADAP KEMUNGKINAN PRAKTIK PERATAAN LABA PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA - Ratna Kumaladewi, Patricia (Jurnal Ilmiah Akuntansi dan Bisnis; Vol 5 No 2 (2010))
The objective of this research was to prove the influence of ReturnOn Assets (ROA) changes, Operating Profit Margin (OPM) changes, andthe size of the company towards the probability of income smoothingpractice. Income smoothing practice is a practice used by the managers ofa company to reduce the fluctuation of the reported income so as toincrease investors’ abilities to forecast the companies’ cash flows in thefuture. Index Eckel was used to determine the income smoothing practice.This research was carried out by using 90 manufacture companieslisted in Indonesia Stock Exchange during 5 years period from 2003 until2007. The hypotheses were tested using binary logistic regression.The first hypothesis was done to prove the positive influence ofROA changes towards the probability of income smoothing practice. Thesecond hypothesis was conducted to examine the positive influence ofOPM changes towards the probability of income smoothing practice. Thelast hypothesis was carried out to test the positive influence of the size ofthe company towards the probability of income smoothing practice. Theresult of this research indicated that 54 out of 90 companies which wereused as samples committed income smoothing practices. The output ofbinary logistic regression showed that ROA changes and OPM changeshad positive effects towards the probability of income smoothing practice.However, the size of the company did not affect the probability of incomesmoothing practice.
Keywords: ROA changes, Operating Profit Margin (OPM) changes, the size of the company, the probability of income smoothing practice